Estabilidade do suco de pitaya vermelha (Hylocereus costaricencis) em diferentes luminosidades - SILVA, Carla Rafaela Fonseca da (2019)
From the advance of new technologies, the market for natural dyes has aroused great interest in industries, especially foods. In order to replace the artificial dyes used, considered harmful to health. Natural dyes give the product a more natural appearance, in which the consumer market searches for products in which they have a good nutritional composition, the presence of minerals, vitamins and other essential substances for the proper functioning of the human organism. In these circumstances, the fruit (Hylocereus costaricensis), known as pitaya, was used to obtain juice (dye). The physical and physico-chemical characterization of the fruit is then carried out, the stability of the betacyanin concentration content and the color of the dye in different luminosities, identifying betacyanin contents by means of UV spectrophotometry and the color by colorimetry Tristimulus, using the CIE system L * a * b *. Evaluating the behavior of betacyanine degradation kinetics using mathematical models.